Pengaruh Social Media Marketing Terhadap Keputusan Berinvestasi Di Pasar Modal Syariah - Ritha Yolanda; Rika Lidyah; Lemiyana (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the effect of social media marketing on investment decisions in the islamic capital market. There are six variables used in this study, namely Online Communities (X1), Interaction (X2), Sharing of Content (X3), Accessibility (X4), Credibility (X5), and Investment Decision (Y). This research was conducted with a quantitative approach using primary data. Primary data obtained through books, journals that support research. The population in this study were students majoring in Business Management at the Sriwijaya State Polytechnic. Then te sampel used was 91 respondents. The sampling technique used is purposive sampling. The analysis used in this research is instrument test, classical assumption test, hypothesis test, and multiple linear regression analysis. The result of the study show that the variables online communities, interaction, sharing of content, accessibility, and credibility simultaneously influence the decision to invest in the Islamic capital market with a value of Fcount > Ftable, namely (7,606>2,32). Meanwhile, the partial tet results show that only the accessibility variable with tcount > ttable (2,241>1,992) has a significant effect on the decision to invest in the islamic capital market.